2016
DOI: 10.1002/ajmg.a.37799
|View full text |Cite
|
Sign up to set email alerts
|

Is one diagnosis the whole story? patients with double diagnoses

Abstract: One of the goals of evaluating a patient in the genetics clinic is to find the diagnosis that would explain his or her clinical presentation. Sometimes the patient's diagnosis remains undefined or does not explain all of the clinical findings. As clinicians are often guided by a "single disorder" paradigm, diagnosing multiple genetic conditions in the same patient requires a heightened sense of awareness. Over the last few years, we evaluated several patients (n = 14) who were found to have more than one genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…Other case studies have revealed at least 3 patients (2 male, 1 female) with a small deletion of a chromosome harbouring genes implicated in hereditary nonpolyposis colorectal cancer (2p, 3p, 7p) who also had IDs and developed colon cancer, 2 of them early in life [41][42][43]. For example, a male patient with a mutation in the PMS2 gene was diagnosed with a rectal carcinoma aged 14 years [44], whilst a man with mild to moderate ID due to Williams syndrome and Lynch syndrome (which increases the risk for colon neoplasia) developed a colorectal cancer aged 37 years [45]. In a Danish cohort of 597 women with Turner syndrome, those who presented with mild IDs were found to be at a higher risk of colon cancer compared to women in the general population [46].…”
Section: Genetic Conditionsmentioning
confidence: 99%
“…Other case studies have revealed at least 3 patients (2 male, 1 female) with a small deletion of a chromosome harbouring genes implicated in hereditary nonpolyposis colorectal cancer (2p, 3p, 7p) who also had IDs and developed colon cancer, 2 of them early in life [41][42][43]. For example, a male patient with a mutation in the PMS2 gene was diagnosed with a rectal carcinoma aged 14 years [44], whilst a man with mild to moderate ID due to Williams syndrome and Lynch syndrome (which increases the risk for colon neoplasia) developed a colorectal cancer aged 37 years [45]. In a Danish cohort of 597 women with Turner syndrome, those who presented with mild IDs were found to be at a higher risk of colon cancer compared to women in the general population [46].…”
Section: Genetic Conditionsmentioning
confidence: 99%
“…The affected individuals in Families II and III do not carry mutations in CYP17A1 or have CAH, suggesting the presence of two independent and unrelated conditions in Family I. The co-occurrence of multiple monogenic disorders is not uncommon among this highly consanguineous population (Kurolap et al, 2016).…”
Section: Resultsmentioning
confidence: 84%
“…In a previous publication we reported that founder mutations and consanguinity are two factors that should raise the index of suspicion for a double diagnosis. 10 These possible diagnostic errors emphasize the importance of a non-biased analysis provided by WES.…”
Section: Discussionmentioning
confidence: 99%